The significant expression of TRPV3 in nasal polyps of eosinophilic chronic rhinosinusitis - Takahiro Tokunaga; Takahiro Ninomiya; Yukinori Kato; Yoshimasa Imoto; Masafumi Sakashita; Tetsuji Takabayashi; Emiko Noguchi; Shigeharu Fujieda (Allergology International, 2017)
Background: The number of patients with eosinophilic chronic rhinosinusitis (ECRS) has been increasing in recent years in Japan. In ECRS, nasal polyps recur immediately after endoscopic sinus surgery. The molecular biological mechanism underlying the refractoriness of ECRS is unclear. Methods: Whole-transcriptome analysis with next-generation sequencing (RNA-seq) was conducted to investigate the molecular biological mechanism of ECRS. Real-time PCR, immunohistochemical staining, and immunofluorescence staining were performed to validate the results of RNA-seq. Results: RNA-seq analysis revealed that in the nasal polyps of ECRS, the levels of 3 transcripts were elevated significantly and those of 7 transcripts were diminished significantly. Among the genes encoding these transcripts, TRPV3 (transient receptor potential cation channel, subfamily V, member 3) was identified as the only gene that is highly expressed in ECRS nasal polyps but this gene's expression was not previously detected using DNA microarray analysis in peripheral blood eosinophils. TRPV3 is newly identified here as a gene transcribed in ECRS. Our analysis also revealed that TRPV3 was highly expressed in the infiltrating eosinophils and mucosal epithelium of the nasal polyps of ECRS, and further that the more severe the refractoriness was after surgery, the higher the TRPV3 expression was in nasal polyps. Conclusions: TRPV3 might play a role in the refractoriness of ECRS. Additional studies are required to evaluate the function of TRPV3 in ECRS.